Migration and emission of mercury from circulating fluidized bed boilers co-firing petroleum coke and coal - Cui, Jian; Duan, Lunbo; Jiang, Ying; Zhao, Changsui; Anthony, Edward J. (Elsevier, 2017)
The migration and emission of mercury (Hg) were studied for three 410 t/h circulating fluidized bed (CFB) boilers co-firing petroleum coke and coal. Both the Ontario Hydro Method (OHM) and US Environmental Protection Agency (EPA) Method 30B were employed to sample gas phase emissions of mercury from the flue gas, and to compare the agreement for these different measurement methods in industrial application. Concurrent with flue gas sampling, solid and liquid samples including fuel, bottom ash, fly ash and gypsum, wastewater, etc., were also collected to determine the total mass balance and map the mercury migration from the power plant. The results showed that the mass balance rates ranged from 83.9% to 122.7%, which can be considered to be both acceptable and reliable. The vast majority of mercury emitted was distributed in the fly ash and stack gas, accounting for 61.36–67.71% and 22.22–33.35%, respectively. The total Hg concentration measured by OHM is comparable with that determined by EPA Method 30B; however, EPA Method 30B possesses advantages in terms of flexibility. The fabric filter (FF) has better Hg0 and Hg2+ removal efficiencies than the electrostatic precipitator (ESP). Because the Hg contained in the liquid waste streams greatly exceeded Chinese regulations, the main emphasis of future work should be focused on wastewater treatment. The mercury emission factors in this study are in the range of 0.69 g/TJ-0.80 g/TJ, which provides basic data for such CFB power plants in China. The CFB boilers equipped with ESP + WFGD or FF + WFGD appear to have the potential to significantly reduce Hg emission to the atmosphere.
Keywords: Hg; Circulating fluidized bed; Co-firing of petroleum coke and coal; Migration; Emission factors